Morphology and Biochemistry of Ovulation - Medeiros, Sebastião Freitas de; Barbosa, Bruna Barcelo; Medeiros, Matheus Antonio Souto de; Yamamoto, Márcia Marly Winck (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
The process of ovulation involves multiple and iterrelated genetic, biochemical, and morphological events: cessation of the proliferation of granulosa cells, resumption of oocyte meiosis, expansion of cumulus cell-oocyte complexes, digestion of the follicle wall, and extrusion of the metaphase-II oocyte. The present narrative review examines these interrelated steps in detail. The combined or isolated roles of the follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are highlighted. Genes indiced by the FSH genes are relevant in the cumulus expansion, and LH-induced genes are critical for the resumption of meiosis and digestion of the follicle wall. A non-human model for follicle-wall digestion and oocyte release was provided.
Keywords: granulosa cells; follicle-stimulating hormone; luteinizing hormone; oocytes; ovarian follicle